Islamic Education Teachers' Strategies in Increase Performance Study Student through Utilization of Padlet Media at SMAN 4 Kota Bima - Wahyuningsih; Syafruddin; Kaharuddin (Lembaga Bale Literasi, 2025)
Study This aim For reviewing PAI Teacher Strategies in Increase Performance Study Student through Utilization of Padlet Media at SMAN 4 Bima City. Research This use approach qualitative, with data collected through interviews, observations, and documentation. Research results show that Islamic Education teacher strategies in increase performance Study student through Padlet utilization is carried out through planning mature learning, presentation? interactive materials, enhancement? activeness and collaboration students, facilitation learning independent, implementation effective evaluation, as well as giving bait come back quickly. Through this strategy, Padlet is able to become a digital learning media that supports improvement understanding, motivation, and achievement Study students in the eye Islamic Religious Education lessons.